Code-Switching in Digital Communication: A Pragmatic Approach to Multilingual Interactions on Social Media - Benny, N Solomon (South Asian Journal of Social Sciences and Humanities, 2025)
This study explains the pragmatic functions of code-switching in multilingual social media interactions, with a specific focus on how social media users employ language alternation to achieve specific communicative functions. The study employs a mixed-methods approach to examine 500 multilingual social media updates, identifying trends and patterns of code switching use. The findings show that code-switching serves significant pragmatic functions, including marking identity, marking solidarity, and negotiating power relations. In addition, the study outlines the significance of digital affordances such as hashtags, emojis, and character limits in shaping code-switching behaviour. The study also highlights the role of code switching in identity construction in the multilingual context, as users combine languages to mark cultural membership and navigate the complexities of living in a multilingual society. The study contributes to the growing body of literature on multilingualism and online communication, shedding new light on the intersection of social interaction, language, and technology. Implications for educators, policymakers, and technology developers are explored for the practical application of multilingual communication in online environments. Despite the limitations inherent in the single case focus and the reliance on publicly available information, the research provides a starting point for studies on code-switching in the multiple linguistic and digital contexts. The findings highlight the importance of inclusive education in language, enabling social media as a widely used medium that is accessible and inclusive of people with diverse linguistic backgrounds.